Kinematical effects of rifle carriage on roller skiing in well-trained female and male biathletes. - Jonsson Kårström, M.; Stöggl, T.; Lund Ohlsson, M.; McGawley, K.; Laakson, M.S. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Purpose This study aimed to investigate how rifle carriage and skiing speed during biathlon roller-skiing affect range of motion (ROM) in joint angles and equipment (skis and poles), the vertical distance between shoulders and treadmill (vertdist), as well as possible sex differences associated with rifle carriage.